Different soil potassium fractions and their contribution towards its uptake under long-term rice-rice cropping system in an Inceptisol of subtropical eastern India - Nayak, Raghabananda; Rout, Kumbhakarna; Mandal, Mitali; Dash, Abhiram (ORYZA-An International Journal of Rice, 2021)
A pot culture experiment was conducted by taking soils from a long term fertilizer experimental field to evaluateÂ the contribution of different K fractions towards rice biomass yield and potassium uptake in different long term fertilizer management practices. Twelve different soils were taken for pot culture and graded dose of potassiumÂ @ 0, 20, 40, 60, 80 and 100 kg K2O ha-1 was applied. Rice variety Lalat was grown as test crop. The forms ofÂ potassium were determined in the surface soil of 0-15 cm after maturity of crop. The result shows that waterÂ soluble form of K is the major contributor to biomass yield in soils taken from100% PK, 100% NPKZn, 100%Â NPKZnB,100% NPKZnS,100% NPK lime and control treated plots of the main field where as exchangeable K is dominant form of K in 100% NPK and 150% NPK. Ammonium acetate K contributes to yield in NPKFYM limeÂ treatment. The nitric acid extractable K is a major contributor to yield in 100% NPKFYM,100% N or100% NPÂ treatment. The water soluble form of K is the major source towards uptake in 150% NPK, NPKFYM lime ,100%Â NPKZnB, or control. Ammonium acetate K becomes the main source by applying 100% PK,100% NPK,100%Â NPKZn,100% NPKZnSor 100% NPKlime whereas exchangeable K becomes major contributor by100%N,orÂ 100% NP application and 1 N HNO3 extractable K is the main source of K uptake in NPKFYM treatment.Â Therefore due importance of different form of potassium should be given in soil test value for better fertilizer management.